Malay Language Teachers' Instructional Leadership and Attitude - Mohd Khairuddin Abdullah; Halimah Laji (Fakulti Pendidikan, UKM, 2014)
This study aims to investigate the relationship between teacher instructional leadership and attitude of Malay Language teachers who are teaching in Sabah primary school. The quantitative methodology used in this study, comprises of survey and co-relational methods. The respondents in this study comprised of 429 primary school teachers in Sabah. The sample was selected using stratified random sampling technique. A set of questionnaire containing 86 items using Likert Scale was used to measure the respondents' feedback. The data was analyzed using SPSS. Descriptive and inferential statistics comprising of Pearson correlation, and one-way ANOVA were used to test the research hypotheses. The result of this study are as follow: (i) a high mean score of instructional leadership and teachers attitude (ii) Pearson correlation showed a significance correlation between instructional leadership and teachers attitudes, and (iii) One way ANOVA analysis did not show any significant difference between teacher instructional leadership with teacher professional qualification and years of teaching bahasa Melayu subject.